Building climate-smart fisheries in Australia: insights from climate and ecosystem status reports - Stephanie Brodie; Laura K. Blamey; Alistair J. Hobday; Éva Plagányi; Daniel Corrie; Natalie Couchman; Alice McDonald; Campbell Davies; Ryan A. Downie; J. Paige Eveson; Elizabeth A. Fulton; Jason R. Hartog; et al. (Reviews in Fish Biology and Fisheries, 2026)
Ongoing concerns about the impact of climate change on Australia’s oceans has driven a request from fisheries managers for improved science communication to the seafood sector. Despite these concerns, translating climate science into management and industry action at regional and sectoral scales remains a challenge. We developed a reporting structure for communicating climate and ecosystem status to fisheries management, industry, and research stakeholders. Our reports consider historical climate impacts, ecosystem indices derived from scientific observing programs, anecdotal on-the-water observations from industry, and forecast climate outlooks tailored for the upcoming fishing season. We developed and delivered reports across 10 diverse fishery case studies, spanning multiple spatial scales and regions (from the tropical north to the temperate south and sub-Antarctic islands) and target species (encompassing benthic invertebrates, demersal fish and sharks, and pelagic billfish and tunas). Here, we describe the reporting structure, the climate and ecosystem indices used, as well as key lessons from the development and dissemination of reports. Key lessons include: (1) Developing tailored environmental indices enhances relevance; (2) Ecosystem observations are essential but remain spatially and temporally patchy; (3) Fishery-independent surveys provide vital data; (4) Remote climate drivers must be considered; (5) Seasonal forecasts offer actionable insights for short-term planning; (6) Fisher observations provide context-rich information that should be systematically incorporated. The lessons and general reporting structure can be applied to the development of other climate and integrated ecosystem reporting activities that are ongoing around the world. We contend that these reports serve as important tools for fostering climate resilience and facilitating the adaptation of the Australian seafood sector to the short and long-term challenges of rapidly changing ocean ecosystems.

An experimental approach to assess the combined effects of multiple stressors on a large vertebrate species - Enrico Pirotta; Catriona M. Harris; Lori H. Schwacke; Len Thomas; Jason B. Allen; Aaron A. Barleycorn; Marco Casoli; Jonathan Crossman; Laura Aichinger Dias; Laura Engleby; Erin LaBrecque; Jenny A. Litz; et al. (Conservation Biology, 2026)
The design of experiments to investigate the combined effects of multiple stressors requires exposing target organisms to multiple combinations of stressor doses. Concurrent manipulation of stressors is often infeasible with wildlife, but long‐lasting health effects allow individual health to be used as an integrator of prior stressor exposure. The population of bottlenose dolphins in Barataria Bay, Louisiana, experienced long‐lasting health effects after exposure to oil from the Deepwater Horizon spill. We investigated whether compromised health status affects dolphins’ ability to respond to other stressors, specifically vessel traffic, potentially leading to increased collision risk. We used this case study to develop a hypothesis‐driven experimental approach to assess the combined effects of multiple stressors in a large, long‐lived vertebrate species. We conducted controlled vessel approaches to test whether the health status of targeted dolphins affected their behavioral responses. Our results highlighted some effects of health, suggesting that oil spills may exacerbate the effects of other stressors in coastal populations. For example, lung disease was associated with a delayed dive response, which could affect the ability to vertically avoid vessels and lead to increased collision risk. However, health effects on response probability were overall smaller than anticipated, and other contextual variables (e.g., sex, age, calf presence, prior experience, and exposure context) contributed to response variability. Our work demonstrated the value of formalizing stressor interactions as multidimensional dose–response functions and showed the feasibility of an experimental, multiple‐stressor study in a wild system in which individual health status can be used as an integrator of prior stressor exposure. This approach has broad implications for other species that are difficult to handle experimentally. The quantification and management of the cumulative risk from multiple stressors on wildlife will require a combination of empirical and mechanistic approaches to inform long‐term, population consequences.

Dietary nitrate supplementation does not improve resistance exercise performance in resistance-trained women - Sydney N. Brennan; Justin M. Foster; Raymond T. Gerardo; Trevor J. Molnar; Ryan Tran; Christopher B. Sottile; Kyle S. Geppert; Michael Egiazarian; Abigail F. Ballhagen; Money Ghimire; John R. M. Renwick; Lewis A. Gough; et al. (European Journal of Applied Physiology, 2026)

High-resolution MRI evidence for age- and sex-related changes in hippocampal subfield volume during healthy aging - Megan C. Hall; Giorgia Picci; Maggie P. Rempe; Jason A. John; Lauren K. Webert; Kellen M. McDonald; Hannah J. Okelberry; Hallie J. Johnson; Lucy K. Horne; Madelyn P. Willett; Ryan J. Glesinger; Danielle L. Rice; et al. (GeroScience, 2026)

Identifying and reporting dystocia in laboratory rodents - Paul Barrow; Prägati S. Coder; Rashin Ghaffari; Leah Zorrilla; Christopher J. Bowman; Curtis E. Grace; Jason Manton; Alan Hoberman; Narinder Barraclough; Isabelle Leconte; Nicola Powles-Glover; Connie Chen; et al. (Reproductive Toxicology, 2026)

Global perspective on the genetic architecture of susceptibility to spot form net blotch in barley - Michele C. Malvestiti; Sefunmi Alaofin; Ryan Skiba; Shengming Yang; Jason D. Fiedler; Zhaohui Liu; Timothy L. Friesen (Theoretical and Applied Genetics, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Peracetic acid efficacy and decay kinetics in poultry processing under chiller conditions - Vyshnavi Ciluveru; Jason Simon; Jeffery M. Farber; Shawn D. Ryan; Chandrasekhar R. Kothapalli; Daniel S. Munther (International Journal of Food Microbiology, 2026)

Wave-induced horizontal diffusivity from optically sensed dye tracer fields in impermeable beach laboratory experiments - Thomas Pendergast; Ryan P. Mulligan; Benjamin Davidson; Alexandra Schueller; Kelsey Fall; Dawson Ethier; Nimish Pujara; Jack A. Puleo; Jason Olsthoorn (Coastal Engineering, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Inbred source populations result in genetic rescue of imperiled trout populations - Donovan A. Bell; Ryan P. Kovach; Zachary Robinson; Anthony Dangora; Jason Mullen; Alex Poole; Jim Olsen; Ronald Spoon; Coltan Pipinich; Lee Nelson; Andrew R. Whiteley (Biological Conservation, 2026)

Strain Energy Minimization Technique to Design a Surgical Heart Valve Using a Novel Polymer - Jason Beith; J. Ryan Stanfield; Morteza Gharib (Annals of Biomedical Engineering, 2026)

Electrolytic hydrogen production from acidified wastewater effluent - Lin Du; Jinyue Jiang; Guangye Zhou; Yuqing Yan; Ryan S. Kingsbury; Anthony Y. Ku; Zhiyong Jason Ren (Water Research, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Techno-economic analysis and life cycle assessment of algal turf scrubbers treating wastewater effluent for renewable diesel production - Ashley Ryland; Peter H. Chen; Mark Zivojnovich; Sungwhan Kim; Ryan W. Davis; Tyler Eckles; Jason C. Quinn; David Quiroz (Algal Research, 2026)

Chronic cannabis use is associated with alterations in resting-state cerebellar-cortical connectivity - Ilenia Salsano; Giorgia Picci; Nathan M. Petro; Anna T. Coutant; Lucy K. Horne; Jason A. John; Ryan Glesinger; Gaelle Doucet; Tony W. Wilson (Psychopharmacology, 2025)

Alongshore velocities and turbulence in the swash and surf zone forced by oblique, monochromatic waves on smooth and rough impermeable beaches - Alexandra E. Schueller; Thomas Pendergast; Kelsey Fall; Hyungyu Sung; Dawson Ethier; Ryan P. Mulligan; Jason Olsthoorn; Nimish Pujara; Jack A. Puleo (Coastal Engineering, 2025)

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Vulnerability of blue carbon to sea-level rise in coastal freshwater ecosystems - Suvrajit Ghosh; Jonathan Obrist-Farner; Jeffery R. Stone; Marta Wojewódka-Przybył; Ryan Smith; Mark Brenner; Jason H. Curtis; Susan R.H. Zimmerman; Alex Correa-Metrio; Paula Gabriela Echeverría Galindo; Madeline J. Brosky; Robert G. Hatfield; et al. (Science of The Total Environment, 2025)

Repeated barrier drown-out is required to facilitate long-distance migration of a potamodromous fish - Jason D. Thiem; Benjamin G. Fanson; David Ryan; Gavin L. Butler; David A. Crook; Doug J. Harding; Anthony Townsend; Ian J. Wooden; Ivor Stuart (Aquatic Sciences, 2025)
Migratory fish species are highly vulnerable to stream fragmentation. Potamodromous golden perch ( Macquaria ambigua ) inhabit the barrier-laden Murray–Darling Basin (MDB), Australia’s largest river system, and its lifecycle includes a requirement for uninterrupted stretches of flowing water habitat. Owing to these barriers, large-scale connectivity in many regions is limited to periods of high flow events that facilitate barrier drown-out. We undertook a 3-year (2021–2024) study using telemetry to quantify the movements of 150 adult golden perch from the Barwon–Darling River over a period that encompassed numerous high flow events and flooding. Approximately 75% of tagged golden perch undertook movements > 50 km, with > 90% of movements in an upstream direction, extending up to 1500 km and associated with increased river discharge. Tributary entries were detected on multiple occasions, with an apparent preference for specific tributaries. Ten fish migrated > 1000 km upstream across multiple flow events. The results of this study (1) highlight the importance of the Barwon–Darling River and tributaries as a key migration conduit for adult golden perch, (2) demonstrate that multiple flow events are required to achieve large-scale dispersal and (3) provide quantitative flow-movement relationships that can be used to support inter-regional management actions. These management actions might include barrier removal, the construction of fishways and protection of tributary–mainstem flow events.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Environmental salinity differentially impacts branchial and hepatic carbohydrate metabolism in tilapia - Ryan J. A. Chang; Fritzie T. Celino‐Brady; Jason P. Breves; Andre P. Seale (Journal of Fish Biology, 2025)
In response to changes in environmental salinity, euryhaline fishes mobilize energy to support the active transport of ions across osmoregulatory epithelia. Glycogen synthase (GS) and glycogen phosphorylase (GP) are key controllers of carbohydrate metabolism due to their roles in promoting glycogenesis and glycogenolysis, respectively. However, the coordinated responses of GS, GP and glucose transporters (GLUTs) in the liver and gill to changes in salinity remain unresolved. In this study, we initially subjected Mozambique tilapia ( Oreochromis mossambicus ) to unidirectional transfers, either from fresh water (FW) to seawater (SW) or from SW to FW. We then transferred FW‐ and SW‐acclimated tilapia to a tidal regime (TR) where salinity alternated between FW and SW every 6 h. Our goal was to characterize how carbohydrate metabolism is affected by unidirectional and tidal changes in salinity. Whether fish were transferred from SW to FW in a unidirectional manner or to a TR, glucose levels increased after transfer to FW or during the FW phase of the TR (TF). Conversely, hepatic glycogen levels were higher in fish in SW and the SW phase of the TR (TS) than in TF. In both FW and TF, branchial expression of the gill‐specific isoform of GP ( gpg ) was downregulated, while gs was upregulated. Branchial gpg was upregulated in fish unidirectionally transferred from FW to SW or sampled during TS. Hepatic gp and gs expression increased following transfer from SW to FW. Thus, we consistently found that increases in salinity promoted branchial glycogen breakdown, while decreases in salinity led to hyperglycaemia. Moreover, while branchial glucose transporter 1 ( glut 1 ) expression was downregulated after transfer from FW to SW, glut1 was transiently upregulated in the liver. In both liver and gill, glut1 expression was higher in fish in TF compared to TS. Gill filament explants incubated with cortisol exhibited reduced glut1 expression regardless of medium osmolality. Our collective data indicate that salinity differentially regulates hepatic and branchial carbohydrate metabolism.

Oscillatory Dynamics Serving Verbal Working Memory Differ in People with HIV and Are Linked To Disease Duration - Kellen M. McDonald; Seth D. Springer; Mikki Schantell; Ryan Glesinger; Lucy K. Horne; Hannah J. Okelberry; Jason A. John; Anna T. Coutant; Madelyn P. Willett; Hallie J. Johnson; Rachel K. Spooner; Tony W. Wilson (Journal of Neuroimmune Pharmacology, 2025)
Background Medical advances have greatly improved the quality of life and extended the longevity of people with HIV (PWH). However, many PWH still develop neurocognitive deficits even in the presence of effective viral suppression, with impairments in verbal working memory (VWM) being among the most common. While previous neuroimaging studies have demonstrated altered neural responses during VWM, the underlying temporal dynamics and their relation to clinical indices of HIV remain poorly understood. Hypothesis PWH will have altered neural oscillatory dynamics in brain regions supporting VWM compared to controls, above and beyond the effect of age, and these oscillatory differences will scale with clinical indices of HIV. Methods 166 participants (77 virally-suppressed PWH, 89 demographically-matched controls) completed a VWM task during magnetoencephalography, which was separated into encoding and maintenance phases. Whole-brain, mixed-model ANCOVAs were performed to assess the effects of HIV status on neural dynamics controlling for age. Results PWH performed significantly worse on the task compared to controls. During encoding, there was a significant interaction of group-by-time window, such that PWH had significantly weaker alpha/beta oscillations in the left inferior frontal, superior temporal, and anterior cingulate relative to controls. Further, weaker activity in the anterior cingulate scaled with increased disease duration. PWH also displayed weaker alpha/beta oscillations during maintenance in frontal, temporal, parietal, anterior cingulate, and cerebellar cortices. Conclusions PWH exhibited weaker task-related oscillatory activity during VWM, which was associated with disease duration in the anterior cingulate. Overall, these findings suggest that HIV modulates the neural dynamics underlying VWM, with progressive effects in some areas.

Re-directing mixed-feed deconstruction products to hybrid polyesters: Tolerance windows for commodity plastics reconstruction - Ryan W. Clarke; Briona J. Carswell; Jason S. DesVeaux; Levi J. Hamernik; Clarissa Lincoln; Vinod K. Konaganti; Rufina G. Alamo; Katrina M. Knauer (Resources, Conservation and Recycling, 2025)

Assessing the effects of anthropogenesis on Appalachian flood severity: An eastern Kentucky case study - Meredith L. Swallom; Jason M. Dortch; J. Ryan Thigpen (Geomorphology, 2025)

Rapid changes in terrestrial carbon dioxide uptake captured in near-real time from a geostationary satellite: The ALIVE framework - Danielle Losos; Sadegh Ranjbar; Sophie Hoffman; Ryan Abernathey; Ankur R. Desai; Jason Otkin; Helin Zhang; Youngryel Ryu; Paul C. Stoy (Remote Sensing of Environment, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Motor-Related Neural Dynamics are Modulated by Regular Cannabis Use Among People with HIV - Lauren K. Webert; Mikki Schantell; Lucy K. Horne; Jason A. John; Ryan Glesinger; Jennifer O’Neill; Maureen Kubat; Anna T. Coutant; Grace C. Ende; Sara H. Bares; Pamela E. May-Weeks; Tony W. Wilson (Journal of Neuroimmune Pharmacology, 2025)
Recent work has shown that people with HIV (PWH) exhibit deficits in cognitive control and altered brain responses in the underlying cortical networks, and that regular cannabis use has a normalizing effect on these neural responses. However, the impact of regular cannabis use on the neural oscillatory dynamics underlying motor control deficits in PWH remains less understood. Herein, 102 control cannabis users, control nonusers, PWH who regularly use cannabis, and PWH who do not use cannabis performed a motor control task with and without interference during high-density magnetoencephalography. The resulting neural dynamics were examined using whole-brain, voxel-wise statistical analyses that examined the impact of HIV status, cannabis use, and their interaction on the neural oscillations serving motor control, spontaneous activity during the baseline period, and neurobehavioral relationships. Our key findings revealed cannabis-by-HIV group interactions in oscillatory gamma within the prefrontal cortices, higher-order motor areas, and other regions, with the non-using PWH typically exhibiting the strongest gamma interference responses. Cannabis-by-HIV interactions were also found for oscillatory beta in the dorsal premotor cortex. Spontaneous gamma during the baseline was elevated in PWH and suppressed in cannabis users in all regions exhibiting interaction effects and the left primary motor cortex, with spontaneous levels being correlated with behavioral performance. These findings suggest that regular cannabis use has a normalizing effect on the neural oscillations serving motor control and the abnormally elevated spontaneous gamma activity that has been widely replicated in PWH, which may suggest that cannabis has at least some therapeutic utility in PWH.

A method in non-destructive testing for lead shielding exceeding 25 kg/m2 using 18F - Jeremy Berrell; Deborah Carrick; Jason Tse; Elaine Ryan (Physical and Engineering Sciences in Medicine, 2025)
Non-Destructive Testing (NDT) is a commonly used technique for barrier verification within radiation protection, ensuring compliance with national standards and state regulations. There are currently limited published methods in NDT for lead shielding above 25 kg/m 2 , and thus this research aimed to develop a reproducible method to aid in ‘in the field’ NDT for lead barriers exceeding 25 kg/m 2 using a Fluorine-18 ( 18 F) source. Due to the fast decay of 18 F, the data generated within this research was compiled from Monte Carlo (MC) simulations using the PENELOPE engine, and the PENGEOM geometry system to model the proposed empirical setup. The model predicted the Transmission Factor (TF) through area densities (thickness) of lead attenuators up to 302.7 kg/m 2 , with results validated by empirical measurements using a Source-to-Detector Distance (SDD) of 38.1 ± 0.05 cm and 52.7 ± 0.05 cm . However, the study was limited by the chosen activity of 18 F at approximately 180 MBq , where the simulated TF curves demonstrated correspondence of data up to and including area densities of 162.4 kg/m 2 using a 38.1 ± 0.05 cm SDD, and 138.0 kg/m 2 with a 52.7 ± 0.05 cm SDD. Beyond these thicknesses, the empirical transmission curves deviated from simulated curves due to measurable transmissions becoming significantly reduced. This research demonstrated that using SDDs above 23 cm would provide sufficient near narrow beam conditions with the proposed experimental configuration for in-the-field NDT. The research aimed to develop an equation and method for NDT using a 18 F source for lead barriers greater than 25 kg/m 2 , with transmission data to be made available upon request to the author.

Protected area coverage of the full annual cycle of migratory butterflies - Shawan Chowdhury; Marcel Cardillo; Jason W. Chapman; David Green; D. Ryan Norris; Federico Riva; Myron P. Zalucki; Richard A. Fuller (Conservation Biology, 2025)
Effective conservation of migratory species relies on habitat protection throughout their annual cycle. Although protected areas (PAs) play a central role in conservation, their effectiveness at conserving habitats across the annual cycle of migratory species has rarely been assessed. We developed seasonal ecological niche models for 418 migratory butterfly species across their global distribution to assess whether they were adequately represented in the PAs across their full annual cycle. PA coverage was inadequate in at least one season for 84% of migratory butterflies, adequate for only 17% of species in one season, and inadequate for 45% of species in all seasons. There was marked geographic variation in PA coverage: 77% of species met representation targets in Sri Lanka, for example, but only 32% met targets in Italy. Our results suggest that coordinated efforts across multiple countries will be needed to develop international networks of PAs that cover the full annual cycle of migratory insects and that conservation measures, in addition to the establishment and maintenance of PAs, are likely to be needed to effectively conserve these species.

Optimizing per vessel hour capture efficiency for rare, heterogeneously distributed fishes: Invasive grass carp Ctenopharyngodon idella in the Sandusky River - Robert D. Hunter; Song S. Qian; Jason L. Fischer; Ryan Brown; Lucas Nathan; John M. Dettmers; James J. Roberts; Corbin D. Hilling; Matthew R. Acre; Robert Mapes; Ryan Young; Christine M. Mayer (Fisheries Research, 2025)

Remote sensing of electron precipitation mechanisms enabled by ELFIN mission operations and ADCS - Ethan Tsai; Akhil Palla; Austin Norris; James King; Cindy Russell; Sophie Ye; Jiashu Wu; Jason Mao; Sharvani Jha; Chanel Young; Graham Wing; Kevin Lian; et al. (Advances in Space Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Hemisphere- and condition-specific alpha oscillations support semantic and spatial cognition in aging - Maggie P. Rempe; Danae S. Manta; Kayle Cohen; Ryan J. Glesinger; Hannah J. Okelberry; Jason A. John; Anna T. Coutant; Lucy K. Horne; Grant M. Garrison; Kennedy A. Kress; Lucas Weyrich; Chloe C. Casagrande; et al. (GeroScience, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Loss of meltwater from glaciers and snowpack may increase synchrony of river habitats and resources in mountain watersheds - Matthew R. Dunkle; J. Ryan Bellmore; Jason B. Fellman; Eran W. Hood; Christopher C. Caudill (Ecology, 2025)
Stream biogeochemical regimes can vary over short distances in heterogenous landscapes. In many mountainous and high‐latitude watersheds, streams fed by rain and groundwater sources coexist with streams dominated by meltwater from melting glaciers, permafrost, and seasonal snowpack. The distinct physicochemical regimes of meltwater and non‐meltwater fed streams can promote spatial and temporal asynchronies in biotic and abiotic environmental conditions within watersheds that promote ecological heterogeneity and stability. However, fading cryospheric inputs to watersheds threaten to homogenize and synchronize stream habitats and resources. Here, we compared the physicochemical conditions and biomass dynamics of stream food webs (course particulate detritus, periphyton, aquatic invertebrates, and fish) over a meltwater season from April to November in four streams with different predominant sources of runoff, one glacier‐fed, one snow‐fed, one rain‐fed, and one stream transitioning from glacier‐ and snow‐fed to a rain‐fed. We then analyzed the temporal correlation (“synchrony”) of the abiotic and biotic conditions in these streams and evaluated how synchrony might change if certain stream types were lost. We found that glacier‐, snow‐, and rain‐fed streams had distinct temperature, flow, and water chemistry regimes and asynchronous seasonal patterns of detritus, biofilm, aquatic invertebrate, and fish biomass. The strongest differences were associated with the divergence of abiotic and biotic conditions in the glacier‐fed stream relative to the other stream types. Synchrony analysis suggests that the climate‐driven loss of meltwater contributions from the cryosphere may synchronize the seasonal resource dynamics of meltwater and non‐meltwater streams during the primary growing season within and across watersheds. Increasing synchrony of abiotic processes that drive instream production could reduce ecological stability within watersheds as seasonal conditions converge, especially for mobile consumers that will lose the opportunity to integrate resource waves across complex landscapes.

Effects of snake fungal disease (ophidiomycosis) on the skin microbiome across two major experimental scales - Alexander S. Romer; Matthew Grisnik; Jason W. Dallas; William Sutton; Christopher M. Murray; Rebecca H. Hardman; Tom Blanchard; Ryan J. Hanscom; Rulon W. Clark; Cody Godwin; N. Reed Alexander; Kylie C. Moe; et al. (Conservation Biology, 2025)
Emerging infectious diseases are increasingly recognized as a significant threat to global biodiversity conservation. Elucidating the relationship between pathogens and the host microbiome could lead to novel approaches for mitigating disease impacts. Pathogens can alter the host microbiome by inducing dysbiosis, an ecological state characterized by a reduction in bacterial alpha diversity, an increase in pathobionts, or a shift in beta diversity. We used the snake fungal disease (SFD; ophidiomycosis), system to examine how an emerging pathogen may induce dysbiosis across two experimental scales. We used quantitative polymerase chain reaction, bacterial amplicon sequencing, and a deep learning neural network to characterize the skin microbiome of free‐ranging snakes across a broad phylogenetic and spatial extent. Habitat suitability models were used to find variables associated with fungal presence on the landscape. We also conducted a laboratory study of northern watersnakes to examine temporal changes in the skin microbiome following inoculation with Ophidiomyces ophidiicola . Patterns characteristic of dysbiosis were found at both scales, as were nonlinear changes in alpha and alterations in beta diversity, although structural‐level and dispersion changes differed between field and laboratory contexts. The neural network was far more accurate (99.8% positive predictive value [PPV]) in predicting disease state than other analytic techniques (36.4% PPV). The genus Pseudomonas was characteristic of disease‐negative microbiomes, whereas, positive snakes were characterized by the pathobionts Chryseobacterium , Paracoccus , and Sphingobacterium . Geographic regions suitable for O. ophidiicola had high pathogen loads (>0.66 maximum sensitivity + specificity). We found that pathogen‐induced dysbiosis of the microbiome followed predictable trends, that disease state could be classified with neural network analyses, and that habitat suitability models predicted habitat for the SFD pathogen.

“I like seeing people, different cultures, and hearing different music”: Exploring adolescent perspectives of inclusive and healthy high-rise and dense urban environment designs - Adrian Buttazzoni; Lindsey Smith; Ryan Lo; Alexander James David Wray; Jason Gilliland; Leia Minaker (Landscape and Urban Planning, 2025)

Evaluating root strength index as an indicator of landslide-prone slopes in eastern kentucky - Meredith L. Swallom; Hudson J. Koch; Jason M. Dortch; Matt M. Crawford; J. Ryan Thigpen; William M. Andrews (Landslides, 2025)

Linking Fire, Food Webs, and Fish in Stream Ecosystems - David A. Roon; J. Ryan Bellmore; Joseph R. Benjamin; François-Nicolas Robinne; Rebecca L. Flitcroft; Jana E. Compton; Joseph L. Ebersole; Jason B. Dunham; Kevin D. Bladon (Ecosystems, 2025)

Influence of extruded soybean meal with different fat contents and varying oleic acid content on floating fish feed quality and composition - Danny B. Patiño; Ondulla T. Toomer; Thien C. Vu; Edgar O. Oviedo-Rondon; Rouf Mian; Mike Frinsko; Steven Hall; Ryan Kelly; Jason Mann; Michael Joseph (Animal Feed Science and Technology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

First report of accumulation of perfluorooctane sulfonate (PFOS) in platypuses (Ornithorhynchus anatinus) in New South Wales, Australia - Katherine G. Warwick; Ian A. Wright; Jessica Whinfield; Jason K. Reynolds; Michelle M. Ryan (Environmental Science and Pollution Research, 2024)
The platypus ( Ornithorhynchus anatinus ) is a semi-aquatic monotreme that occupies a high trophic position in the freshwater ecosystems of eastern mainland Australia and Tasmania. Platypuses are continuously exposed to anthropogenic contaminants including perfluorooctane sulfonate (PFOS). This study examined PFOS concentrations in the livers of deceased platypuses (eight wild; one captive) that were opportunistically collected across NSW over a two- and a half-year period. There was a large variation in PFOS concentrations, ranging from < 1 µg/kg to 1200 µg/kg. This study presents the first report of PFOS contamination in platypuses, revealing their PFOS levels are broadly similar to those found in river otters ( Lutra canadensis ) and lower than those in American mink ( Mustela vison), both which occupy similar ecological niches in freshwater systems. This study raises concerns about the impact of PFOS on platypus health.

Review of dose setting for the extended one-generation reproductive toxicity studies (OECD TG 443): Considerations on ECHA's dose level selection recommendations - Manon Beekhuijzen; Emily Richmond; Jason Manton; Pragati S. Coder; Katy Goyak; Rashin Ghaffari; Susan L. Makris; Steven Van Cruchten; Leah Zorrilla; Shermaine Mitchell-Ryan (Regulatory Toxicology and Pharmacology, 2024)

fNIRS is capable of distinguishing laterality of lower body contractions - Rob J. MacLennan; Jesus A. Hernandez-Sarabia; Shawn M. Reese; JoCarol E. Shields; Claire M. Smith; Katharina Stute; Jordyn Collyar; Alex A. Olmos; Tyler L. Danielson; Demi L. MacLennan; Jason I. Pagan; Ryan M. Girts; et al. (Experimental Brain Research, 2024)

Factors associated with Paddlefish ( Polyodon spathula ) restoration success in Oklahoma - Ryan A. Gary; James M. Long; Brian T. Eachus; Andrew R. Dzialowski; Jason D. Schooley (Fisheries Management and Ecology, 2024)
The Paddlefish ( Polyodon spathula) has been extirpated from portions of its native range due to anthropogenic habitat degradation and fragmentation, most notably the impoundment of rivers. To mitigate some of these losses in Oklahoma, Paddlefish have been stocked into reservoirs throughout the state, with variable success in establishing self‐sustaining populations. Two factors thought to contribute to success of Paddlefish stocking are spawning substrate and prey availability, which were quantified in six reservoirs and nine reservoir tributaries. Side‐scan sonar and supervised classification of aerial imagery were used to classify 4517‐ha of river substrate upstream of the river‐reservoir interface in reservoir tributaries. Zooplankton community structure, water clarity, and nutrient availability were also assessed in the same reservoirs and tributaries. One tributary had suitable spawning substrate (>40%), and the rest had minimal (

Phytoplankton composition from sPACE: Requirements, opportunities, and challenges - Ivona Cetinić; Cecile S. Rousseaux; Ian T. Carroll; Alison P. Chase; Sasha J. Kramer; P. Jeremy Werdell; David A. Siegel; Heidi M. Dierssen; Dylan Catlett; Aimee Neeley; Inia M. Soto Ramos; Jennifer L. Wolny; et al. (Remote Sensing of Environment, 2024)

Glaciers, snow, and rain: Water source influences invertebrate community structure and secondary production across a hydrologically diverse subarctic landscape - Matthew R. Dunkle; J. Ryan Bellmore; Jason B. Fellman; Christopher C. Caudill (Limnology and Oceanography, 2024)
The melting cryosphere adds heterogeneity to the abiotic and biotic characteristics of many high latitude and montane rivers. However, climate change threatens the cryosphere's persistence in many regions. While existing research has explored the impacts of cryospheric loss on the diversity and structure of freshwater communities, implications for functional traits of communities, such as production of aquatic invertebrates, remain unresolved. Here, we quantified aquatic invertebrate community structure and secondary production in southeast Alaska ( USA ) streams that represent a meltwater to non‐meltwater gradient, including streams fed primarily by: (1) glacier‐melt, (2) snowmelt, (3) rainfall, and (4) a combination of these sources. We found alpha diversity was highest in the snow‐fed stream and lowest in the glacier‐fed stream. Annual secondary production was also lowest in the glacier‐fed stream (0.56 g ash‐free dry mass m −2 ), but 2–5 times higher in the other stream types primarily due to greater production of shared taxa that were found in all streams. However, despite low invertebrate diversity and productivity, the glacier‐fed stream hosted distinct species assemblages associated with unique cycles of stream flow, water temperature, turbidity, and nutrient concentrations, which contributed to higher beta diversity between streams. Our findings suggest that the loss of glacier‐melt contributions to rivers may result in increased freshwater invertebrate production but reduced beta diversity, which could have implications for community stability and the capacity of landscapes to support higher‐level consumers, including fishes.

Developing community-based criteria for sustaining non-timber forest products: A case study with the Missanabie Cree First Nation - Nicholas Palaschuk; Jason Gauthier; Ryan Bullock (Forest Policy and Economics, 2024)

Individual heterogeneity in ixodid tick infestation and prevalence of Borrelia burgdorferi sensu lato in a northern community of small mammalian hosts - Lars K. Lindsø; Jason L. Anders; Hildegunn Viljugrein; Anders Herland; Vetle M. Stigum; W. Ryan Easterday; Atle Mysterud (Oecologia, 2023)
Heterogeneous aggregation of parasites between individual hosts is common and regarded as an important factor in understanding transmission dynamics of vector-borne diseases. Lyme disease is vectored by generalist tick species, yet we have a limited understanding of how individual heterogeneities within small mammal host populations affect the aggregation of ticks and likelihood of infection. Male hosts often have higher parasite and infection levels than females, but whether this is linked to sexual body size dimorphism remains uncertain. Here, we analysed how host species, sex, and body mass influenced Ixodes ricinus tick infestations and the infection prevalence of Borrelia burgdorferi sensu lato (s.l.) in three species of small mammals involved in the enzootic transmission cycle of Lyme disease in Norway from 2018 to 2022. Larval and nymphal ticks were found on 98% and 34% of all individual hosts, respectively. In bank voles and wood mice, both larval and nymphal tick infestation and infection probability increased with body mass, and it increased more with mass for males than for females. Tick infestation in the common shrew increased with body mass and was higher in males, while pathogen infection was higher in females. Sex-biases in infestation did not correspond with level of sexual body mass dimorphism across species. This study contributes to our understanding of how individual heterogeneity among small mammalian hosts influences I. ricinus tick aggregation and prevalence of B. burgdorferi s.l. at northern latitudes.

Evaluation of an in vitro experimental platform of human polarized intestinal epithelial monolayers for the hazard assessment of insecticidal proteins - Cindi S. Zimmermann; Ryan F. Snow; Brittany Wilson-Mifsud; Kristine LeRoy; Chad Boeckman; Emily Huang; Carey A. Mathesius; Jason M. Roper; Bryan P. Hurley (Food and Chemical Toxicology, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

A comparison of techniques for verifying the accuracy of precision decomposition-derived relationships between motor unit firing rates and recruitment thresholds from surface EMG signals - Jonathan P. Beausejour; Paul Bohlen; Kylie K. Harmon; Ryan M. Girts; Jason I. Pagan; Debbie L. Hahs-Vaughn; Trent J. Herda; Matt S. Stock (Experimental Brain Research, 2023)

Correlated responses to selection for different cell size in Chlamydomonas reinhardtii using divergent evolutionary pathways - Wladimir A. Fae Neto; Ryan Dosselli; W. Jason Kennington; Joseph L. Tomkins (Journal of Applied Phycology, 2023)
Cell size is an important trait that is often correlated with organisms’ survival under different thermal environments, and in the case of phytoplankton, it is also related to survival under different light irradiance. While smaller phytoplankton thrive under warm and high light (summer conditions), larger cells seem to be more efficient under cool and low light conditions (winter conditions). In this study, we used different evolutionary pathways, nitrogen depletion and size selection, to select for differences in average cell diameter in the single-celled alga Chlamydomonas reinhardtii. We tested whether there was a size-related fitness (growth rate) advantage across two light intensities and two temperatures; environmental effects that have dramatic effects on algal growth. Under these environmental conditions we then tested how the evolutionary pathway to reduced cell size affected fitness and photophysiology. The results suggest that the relationship between size and growth rate in C. reinhardtii is strongly correlated with changes in the photosynthetic apparatus in different sized cells. Large-selected cells evolved to have smaller light-harvesting antennae, making them less susceptible to photodamage. However, they accumulate larger amounts of reactive oxygen species, potentially due to their lack of antioxidant carotenoids. In addition, the maximum growth rate was reduced, potentially due to their reduced ability to repair PSII due to lower metabolic rates. Similar responses were observed in lines that evolved to have smaller cells under nitrogen depletion. The results demonstrate that different evolutionary pathways to reduced cell size result in different changes in metabolism, with N-depleted and Small-selected cell lineages having similar sizes, but thriving differently under winter/summer conditions. With large production systems in mind, it is possible to assume that the choice of strains selected using adaptative laboratory evolution or direct selection on size can affect the overall production yield and carbon capture according to the seasons and possibly other abiotic parameters.

Discovery of pyrrolo[2,1-f][1,2,4]triazine-based inhibitors of adaptor protein 2-associated kinase 1 for the treatment of pain - Carolyn D. Dzierba; Bireshwar Dasgupta; George Karageorge; Walter Kostich; Brian Hamman; Jason Allen; Kim M. Esposito; Ramesh Padmanabha; James Grace; Kimberley Lentz; John Morrison; Daniel Morgan; et al. (Medicinal Chemistry Research, 2023)

Site-specific factors override local climatic conditions in determining microalgae productivity in open raceway ponds - Isidora Echenique-Subiabre; Jonah M. Greene; Aidan Ryan; Heather Martinez; Marcela Balleza; Julia Gerber; Ahlem Jebali; Stephanie Getto; Charles J. O'Kelly; Shovon Mandal; Jason C. Quinn; Shawn R. Starkenburg; et al. (Algal Research, 2023)

Corrigendum to “A functional size-spectrum model of the global marine ecosystem that resolves zooplankton composition”, Ecological Modelling, 2020, 435: 109265 - Ryan F. Heneghan; Jason D. Everett; Patrick Sykes; Sonia D. Batten; Martin Edwards; Kunio Takahashi; Iain M. Suthers; Julia L. Blanchard; Anthony J. Richardson (Ecological Modelling, 2023)

Viability of side-scan sonar to enumerate Paddlefish, a large pelagic freshwater fish, in rivers and reservoirs - Wyatt Wolfenkoehler; James M. Long; Ryan Gary; Richard A. Snow; Jason D. Schooley; Lindsey A. Bruckerhoff; Robert C. Lonsinger (Fisheries Research, 2023)

Genetic and physical localization of a major susceptibility gene to Pyrenophora teres f. maculata in barley - Abdullah F. Alhashel; Jason D. Fiedler; Raja Sekhar Nandety; Ryan M. Skiba; Robert S. Bruggeman; Thomas Baldwin; Timothy L. Friesen; Shengming Yang (Theoretical and Applied Genetics, 2023)
Key message Genetic characterization of a major spot form net blotch susceptibility locus to using linkage mapping to identify a candidate gene and user-friendly markers in barley. Abstract Spot form net blotch (SFNB), caused by the necrotrophic fungal pathogen Pyrenophora teres f. maculata ( Ptm ), is an economically important foliar diseases in barley. Although various resistance loci have been identified, breeding for SFNB-resistant varieties has been hampered due to the complex virulence profile of Ptm populations. One resistance locus in the host may be effective against one specific isolate, but it may confer susceptibility to other isolates. A major susceptibility QTL on chromosome 7H, named Sptm1 , was consistently identified in many studies. In the present study, we conduct fine mapping to localize Sptm1 with high resolution. A segregating population was developed from selected F 2 progenies of the cross Tradition (S) × PI 67381 (R), in which the disease phenotype was determined by the Sptm1 locus alone. Disease phenotypes of critical recombinants were confirmed in the following two consecutive generations. Genetic mapping anchored the Sptm1 gene to an ⁓400 kb region on chromosome 7H. Gene prediction and annotation identified six protein-coding genes in the delimited Sptm1 region, and the gene encoding a putative cold-responsive protein kinase was selected as a strong candidate. Therefore, providing fine localization and candidate of Sptm1 for functional validation, our study will facilitate the understanding of susceptibility mechanism underlying the barley- Ptm interaction and offers a potential target for gene editing to develop valuable materials with broad-spectrum resistance to SFNB.

Geographically-resolved evaluation of the economic and environmental services from renewable diesel derived from attached algae flow-ways across the United States - Austin B. Banks; Peter H. Chen; Carlos Quiroz-Arita; Ryan W. Davis; Jason C. Quinn (Algal Research, 2023)

Chromosome-length genome assemblies and cytogenomic analyses of pangolins reveal remarkable chromosome counts and plasticity - Marlys L. Houck; Klaus-Peter Koepfli; Taylor Hains; Ruqayya Khan; Suellen J. Charter; Julie A. Fronczek; Ann C. Misuraca; Sergei Kliver; Polina L. Perelman; Violetta Beklemisheva; Alexander Graphodatsky; Shu-Jin Luo; et al. (Chromosome Research, 2023)

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

Glacier runoff influences biogeochemistry and resource availability in coastal temperate rainforest streams: Implications for juvenile salmon growth - Jason B. Fellman; J. Ryan Bellmore; Connor Johnson; Matthew R. Dunkle; Eran Hood (Limnology and Oceanography, 2023)
Meltwater contributions to watersheds are shrinking as glaciers disappear, altering the flow, temperature, and biogeochemistry of freshwaters. A potential consequence of this landscape change is that streamflow patterns within glacierized watersheds will become more homogenous, potentially altering the capacity of watersheds to support Pacific salmon. To assess heterogeneity in stream habitat quality for juvenile salmon in a watershed in the Alaska Coast Mountains, we collected organic matter and invertebrate drift and measured streamwater physical and biogeochemical properties over the main runoff season in two adjacent tributaries, one fed mainly by rain and the other partially by glacier ice/snowmelt. We then used bioenergetic modeling to evaluate how temporal patterns in water temperature and invertebrate drift in each tributary influence juvenile salmon growth potential. Across the study period, average invertebrate drift concentrations were similar in non‐glacierized Montana (0.33 mg m −3 ) and glacier‐influenced McGinnis Creeks (0.38 mg m −3 ). However, seasonal patterns of invertebrate drift were temporally asynchronous between the two streams. Invertebrate drift and modeled fish growth were generally higher in McGinnis Creek in the spring and Montana Creek in the Summer. For juvenile salmon, tracking these resource asynchronies by moving between tributaries resulted in 20% greater growth than could be obtained within either stream alone. These results suggest that hydrologic heterogeneity within watersheds may enhance the diversity of foraging and growth opportunities for mobile aquatic organisms, which may be essential for supporting productive and resilient natural salmon runs.

Host and pathogen genetics reveal an inverse gene-for-gene association in the P. teres f. maculata–barley pathosystem - Ryan M. Skiba; Nathan A. Wyatt; Gayan K. Kariyawasam; Jason D. Fiedler; Shengming Yang; Robert S. Brueggeman; Timothy L. Friesen (Theoretical and Applied Genetics, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Visual Estimation Accuracy of Tree Part Diameter and Fall Distance - Ryan W Klein; Drew C McLean; Andrew K Koeser; Richard J Hauer; Jason W Miesbauer; Allyson B Salisbury (Journal of Forestry, 2022)
When professionals assess tree risk, they must consider the potential consequences associated with a branch or whole tree striking a person, vehicle, or structure. This process requires an assessor to determine the diameter and fall distance of a tree part and then gauge the likely damage to a target if failure occurred. The ability to accurately estimate diameter and fall distances is important, as direct measurements are not always possible. In this study, we examined whether differences exist between visual estimations and direction measurements of tree part diameters and fall distances among 106 arborists of differing experience levels. Our findings suggest arborists’ estimations were reasonably accurate in comparison to direct measurements. International Society of Arboriculture Certified Arborists and experienced arborists were more accurate in diameter estimations than arborists lacking assessment experience. In contrast, nonexperienced arborists were closer in their fall distance estimations than arborists with risk assessment experience.

Multi-habitat seascape restoration: optimising marine restoration for coastal repair and social benefit - Dominic McAfee; Patrick Reis-Santos; Alice R. Jones; Bronwyn M. Gillanders; Camille Mellin; Ivan Nagelkerken; Melissa J. Nursey-Bray; Ryan Baring; Graziela Miot da Silva; Jason E. Tanner; Sean D. Connell (Frontiers in Marine Science, 2022)
Marine ecosystem restoration is fast becoming the primary tool for repairing the socio-ecological functions and economic benefits of coastal ecosystems. Healthy seascapes are characterized by many interacting species and intermingled habitats (e.g., seagrass, kelp, shellfish, sedimentary) that co-create ecological functions of substantial socio-economic value. These co-created functions not only build stability and resilience at seascape scales, but synergistically combine to enhance ecological productivity that is greater than the sum of the individual habitats. Yet, restoration practice is dominated by single-habitat approaches underpinned by single-species monocultures, potentially limiting the range of benefits that restoration can provide. We propose that for ecosystem restoration to meet its full potential in delivering socio-ecological benefits that are resilient to environmental change, restoration practices should plan beyond single-species and single-habitats to a multi-habitat seascape. Where multiple habitats are co-restored, their positive interactions mutually benefit each other to stabilize and even accelerate ecosystem recovery; such as co-restored shellfish and kelp forests on constructed reefs, which combine to stabilize sediment for seagrass recovery. As fisheries scientists and managers, food and social scientists, and ecologists and oceanographers, we describe multi-habitat marine restoration activities that are readily achievable and provide a vision for the diverse socio-ecological, economic, and culture benefits that may emerge from future seascape-level repair.

A melting cryosphere constrains fish growth by synchronizing the seasonal phenology of river food webs - J. Ryan Bellmore; Jason B. Fellman; Eran Hood; Matthew R. Dunkle; Richard T. Edwards (Global Change Biology, 2022)
Mountain watersheds often contain a mosaic of glacier‐, snow‐, and rain‐fed streams that have distinct hydrologic, temperature, and biogeochemical regimes. However, as glaciers diminish and precipitation shifts from snow to rain, the physical and chemical characteristics that make glacial or snowmelt streams distinct from rain‐fed streams will fade. Among the unforeseen consequences of this hydrologic homogenization could be the loss of unique food webs that sustain aquatic consumers. To explore the impacts of a melting cryosphere on stream food webs, we parameterized an aquatic food web model with empirical physicochemical data from glacier‐, snow‐, and rain‐fed streams in southeast Alaska and used the model to simulate the seasonal biomass dynamics of aquatic primary producers and consumers and the growth of juvenile salmon. Model results suggest that glacier‐, snow‐, and rain‐fed streams exhibit seasonal asynchronies in the timing of biofilm and aquatic invertebrate abundance. Although warmer rain‐fed streams were more productive during the summer (June through September), colder glacial and snowmelt streams provided enhanced foraging and growth opportunities throughout the remainder of the year. For juvenile salmon that can track peaks in resource abundance within river networks, the loss of meltwater streams strongly constrained modeled growth opportunities by removing spatially and temporally distinct foraging habitats within a watershed. These findings suggest that climate change induced homogenization of high latitude river networks may result in the loss of unique food web dynamics, which could diminish the capacity of watersheds to sustain mobile consumers.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The acute effects of action observation on muscle strength/weakness and corticospinal excitability in older adults - Kylie K. Harmon; Ryan M. Girts; Jason I. Pagan; Gabriela Rodriguez; Matt S. Stock (Experimental Brain Research, 2022)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Two common bee-sampling methods reflect different assemblages of the bee (Hymenoptera: Apoidea) community in mixed-grass prairie systems and are dependent on surrounding floral resource availability - C. K. Pei; Torre J. Hovick; Cameron A. Duquette; Ryan F. Limb; Jason P. Harmon; Benjamin A. Geaumont (Journal of Insect Conservation, 2022)

Population genetic structure of a broadcast‐spawning coral across a tropical–temperate transition zone reveals regional differentiation and high‐latitude reef isolation - Richard D. Evans; Luke Thomas; W. Jason Kennington; Nicole M. Ryan; Nerida G. Wilson; Zoe Richards; Ryan J. Lowe; Chenae Tuckett (Journal of Biogeography, 2021)
Aim Genetic connectivity is a key component of species resilience to climate change in terms of recovery capacity following disturbance and capacity to disperse to novel locations as the climate warms and isotherms shift poleward. We aimed to strengthen our understanding of resilience in this context by characterizing patterns of connectivity and genetic diversity in a broadcast spawning coral across a tropical–temperate transition zone. We hypothesize genetic differentiation between tropical and temperate populations and decreasing genetic diversity with higher latitudes. Location Western Australia (WA). Taxon Turbinaria species complex. Turbinaria ‘reniformis’ Oken, 1815 (Scleractinia: Dendrophylliidae). Methods A total of 930 target corals were sampled from 10 locations between 13 and 32° latitude spanning a 9°C mean temperature range. In situ species identification of T . reniformis is hindered by morphological plasticity and homoplasy with sister species. We combined Sanger sequencing of two mitochondrial DNA markers and high‐throughput genotyping by sequencing (GBS) to isolate a single genetic Turbinaria lineage from our dataset through which patterns of genetic flow and diversity along the WA coastline could be explored using population‐ and individual‐based clustering analyses. Results Mitochondrial DNA sequence variation was low among Turbinaria samples and could not resolve individual species. Using GBS, we identified three genetically distinct lineages. Subsequent analyses within one of these lineages revealed strong spatial subdivision with 2–3 genetic clusters. While temperate populations were genetically diverged from more tropical sites, we did not observe declines in genetic diversity with latitude. Main conclusions Tropical populations of T . ‘reniformis’ in Western Australia exhibit strong genetic connectivity, which extends to a southern limit at sub‐tropical Shark Bay. Temperate populations are genetically isolated from their tropical counterparts but have relatively high genetic diversity. While the maintenance of genetic variation in temperate populations may provide some resilience to future climate scenarios, their isolation may increase their vulnerability.

Improving species status assessments under the U.S. Endangered Species Act and implications for multispecies conservation challenges worldwide - Reed F. Noss; Jennifer M. Cartwright; Dwayne Estes; Theo Witsell; Gregg Elliott; Daniel Adams; Matthew Albrecht; Ryan Boyles; Patrick Comer; Chris Doffitt; Don Faber‐Langendoen; JoVonn Hill; et al. (Conservation Biology, 2021)
Despite its successes, the U.S. Endangered Species Act (ESA) has proven challenging to implement due to funding limitations, workload backlog, and other problems. As threats to species survival intensify and as more species come under threat, the need for the ESA and similar conservation laws and policies in other countries to function efficiently has grown. Attempts by the U.S. Fish and Wildlife Service (USFWS) to streamline ESA decisions include multispecies recovery plans and habitat conservation plans. We address species status assessment (SSA), a USFWS process to inform ESA decisions from listing to recovery, within the context of multispecies and ecosystem planning. Although existing SSAs have a single‐species focus, ecosystem‐based research can efficiently inform multiple SSAs within a region and provide a foundation for transition to multispecies SSAs in the future. We considered at‐risk grassland species and ecosystems within the southeastern United States, where a disproportionate number of rare and endemic species are associated with grasslands. To initiate our ecosystem‐based approach, we used a combined literature‐based and structured World Café workshop format to identify science needs for SSAs. Discussions concentrated on 5 categories of threats to grassland species and ecosystems, consistent with recommendations to make shared threats a focus of planning under the ESA: (1) habitat loss, fragmentation, and disruption of functional connectivity; (2) climate change; (3) altered disturbance regimes; (4) invasive species; and (5) localized impacts. For each threat, workshop participants identified science and information needs, including database availability, research priorities, and modeling and mapping needs. Grouping species by habitat and shared threats can make the SSA process and other planning processes for conservation of at‐risk species worldwide more efficient and useful. We found a combination of literature review and structured discussion effective for identifying the scientific information and analysis needed to support the development of multiple SSAs. Article impact statement : Species status assessments can be improved by an ecosystem‐based approach that groups imperiled species by shared habitats and threats.

Growth of Flavobacterium columnare Genomovars in the Presence or Lack of Supplemental Cations - Jason P. Evenhuis; Ryan Lipscomb; Clayton Birkett (Current Microbiology, 2021)

Virulence variations of Flavobacterium columnare in rainbow trout ( Oncorhynchus mykiss ) eyed eggs and alevin - Jason P. Evenhuis; Ryan Lipscomb; Clayton Birkett (Journal of Fish Diseases, 2021)
Flavobacterium columnare (Fc) is the causative agent for columnaris disease (CD) in several fish species and an emerging problem for rainbow trout aquaculture. We characterize the virulence phenotype of two Fc isolates, CSF‐298–10 and MS‐FC‐4, against trout from two sources, NCCCWA and a production stock (PS), at the eyed egg and alevin life stages. Immersion challenges demonstrated that NCCCWA eyed eggs were susceptible to the Fc isolate MS‐FC‐4 (>97% mortality) but no mortality was observed against PS eyed eggs. The CSF‐298–10 had little effect on any eyed eggs tested and was not highly virulent to any alevin till day six post‐hatch, up to 38% for NCCCWA and ~80% PS alevin. The MS‐FC‐4 strain produced ≥80% mortality any day an immersion challenge occurred post‐hatch. Significant difference in CFU counts was recorded between the Fc strains on 2 days post‐hatch immersion challenges. Counts for the NCCCWA alevin were 4.4 × 10 3 CFU/ml ‐1 and 1.8 × 10 6 CFU/ml ‐1 for the CSF‐298–10 strain and MS‐FC‐4 strain, respectively, and for the PS alevin CSF‐298–10 measured 9.9 × 10 1 CFU/ml ‐1 and 3.8 × 10 5 CFU/ml ‐1 for MS‐FC‐4. These two Fc isolates present stark differences in virulence phenotypes to both eyed eggs and alevin and present an interesting model system for virulence kinetics and potentially alternative pathogenic pathways.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Late-life voluntary wheel running reverses age-related aortic stiffness in mice: a translational model for studying mechanisms of exercise-mediated arterial de-stiffening - Rachel A. Gioscia-Ryan; Zachary S. Clayton; Bradley S. Fleenor; Jason S. Eng; Lawrence C. Johnson; Matthew J. Rossman; Melanie C. Zigler; Trent D. Evans; Douglas R. Seals (GeroScience, 2021)

Bee phenology is predicted by climatic variation and functional traits - Michael Stemkovski; William D. Pearse; Sean R. Griffin; Gabriella L. Pardee; Jason Gibbs; Terry Griswold; John L. Neff; Ryan Oram; Molly G. Rightmyer; Cory S. Sheffield; Karen Wright; Brian D. Inouye; et al. (Ecology Letters, 2020)
Climate change is shifting the environmental cues that determine the phenology of interacting species. Plant–pollinator systems may be susceptible to temporal mismatch if bees and flowering plants differ in their phenological responses to warming temperatures. While the cues that trigger flowering are well‐understood, little is known about what determines bee phenology. Using generalised additive models, we analyzed time‐series data representing 67 bee species collected over 9 years in the Colorado Rocky Mountains to perform the first community‐wide quantification of the drivers of bee phenology. Bee emergence was sensitive to climatic variation, advancing with earlier snowmelt timing, whereas later phenophases were best explained by functional traits including overwintering stage and nest location. Comparison of these findings to a long‐term flower study showed that bee phenology is less sensitive than flower phenology to climatic variation, indicating potential for reduced synchrony of flowers and pollinators under climate change.

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

Unique Post-telemetry Recapture Enables Development of Multi-Element Isoscapes From Barnacle Shell for Retracing Host Movement - Ryan M. Pearson; Jason P. van de Merwe; Michael K. Gagan; Rod M. Connolly (Frontiers in Marine Science, 2020)

Modeling control of Common Carp (Cyprinus carpio) in a shallow lake–wetland system - James Pearson; Jason Dunham; J. Ryan Bellmore; Don Lyons (Wetlands Ecology and Management, 2019)

Regional coral disease outbreak overwhelms impacts from a local dredge project - Brooke E. Gintert; William F. Precht; Ryan Fura; Kristian Rogers; Mike Rice; Lindsey L. Precht; Martine D’Alessandro; Jason Croop; Christina Vilmar; Martha L. Robbart (Environmental Monitoring and Assessment, 2019)

Thermal biology of mosquito‐borne disease - Erin A. Mordecai; Jamie M. Caldwell; Marissa K. Grossman; Catherine A. Lippi; Leah R. Johnson; Marco Neira; Jason R. Rohr; Sadie J. Ryan; Van Savage; Marta S. Shocket; Rachel Sippy; Anna M. Stewart Ibarra; et al. (Ecology Letters, 2019)
Mosquito‐borne diseases cause a major burden of disease worldwide. The vital rates of these ectothermic vectors and parasites respond strongly and nonlinearly to temperature and therefore to climate change. Here, we review how trait‐based approaches can synthesise and mechanistically predict the temperature dependence of transmission across vectors, pathogens, and environments. We present 11 pathogens transmitted by 15 different mosquito species – including globally important diseases like malaria, dengue, and Zika – synthesised from previously published studies. Transmission varied strongly and unimodally with temperature, peaking at 23–29ºC and declining to zero below 9–23ºC and above 32–38ºC. Different traits restricted transmission at low versus high temperatures, and temperature effects on transmission varied by both mosquito and parasite species. Temperate pathogens exhibit broader thermal ranges and cooler thermal minima and optima than tropical pathogens. Among tropical pathogens, malaria and Ross River virus had lower thermal optima (25–26ºC) while dengue and Zika viruses had the highest (29ºC) thermal optima. We expect warming to increase transmission below thermal optima but decrease transmission above optima. Key directions for future work include linking mechanistic models to field transmission, combining temperature effects with control measures, incorporating trait variation and temperature variation, and investigating climate adaptation and migration.

Synergies in Operational Oceanography: The Intrinsic Need for Sustained Ocean Observations - Fraser Davidson; Aida Alvera-Azcárate; Alexander Barth; Gary B. Brassington; Eric P. Chassignet; Emanuela Clementi; Pierre De Mey-Frémaux; Prasanth Divakaran; Christopher Harris; Fabrice Hernandez; Patrick Hogan; Lars R. Hole; et al. (Frontiers in Marine Science, 2019)

Groundwater inflows control patterns and sources of greenhouse gas emissions from streams - Anna Lupon; Blaize A. Denfeld; Hjalmar Laudon; Jason Leach; Jan Karlsson; Ryan A. Sponseller (Limnology and Oceanography, 2019)
Headwater streams can be important sources of carbon dioxide (CO 2 ) and methane (CH 4 ) to the atmosphere. However, the influence of groundwater–stream connectivity on the patterns and sources of carbon (C) gas evasion is still poorly understood. We explored these connections in the boreal landscape through a detailed study of a 1.4 km lake outlet stream that is hydrologically fed by multiple topographically driven groundwater input zones. We measured stream and groundwater dissolved organic C (DOC), CO 2 , and CH 4 concentrations every 50 m biweekly during the ice‐free period and estimated in‐stream C gas production through a mass balance model and independent estimates of aquatic metabolism. The spatial pattern of C gas concentrations was consistent over time, with peaks of both CH 4 and CO 2 concentrations occurring after each groundwater input zone. Moreover, lateral C gas inputs from riparian soils were the major source of CO 2 and CH 4 to the stream. DOC mineralization and CH 4 oxidation within the stream accounted for 17–51% of stream CO 2 emissions, and this contribution was the greatest during relatively higher flows. Overall, our results illustrate how the nature and arrangement of groundwater flowpaths can organize patterns of stream C concentrations, transformations, and emissions by acting as a direct source of gases and by supplying organic substrates that fuel aquatic metabolism. Hence, refined assessments of how catchment structure influences the timing and magnitude of groundwater–stream connections are crucial for mechanistically understanding and scaling C evasion rates from headwaters.

Cross-education: effects of age on rapid and maximal voluntary contractile characteristics in males - Garrett M. Hester; Mitchel A. Magrini; Ryan J. Colquhoun; Alejandra Barrera-Curiel; Carlos A. Estrada; Alex A. Olmos; Alyssa R. Bailly; Phuong L. Ha; Jason M. DeFreitas (European Journal of Applied Physiology, 2019)

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Jittered echo-delay resolution in bottlenose dolphins (Tursiops truncatus) - James J. Finneran; Ryan Jones; Jason Mulsow; Dorian S. Houser; Patrick W. Moore (Journal of Comparative Physiology A, 2019)

Estimating the Usefulness of Chemical Dispersant to Treat Surface Spills of Oil Sands Products - Thomas King; Brian Robinson; Scott Ryan; Kenneth Lee; Michel Boufadel; Jason Clyburne (Journal of Marine Science and Engineering, 2018)
This study examines the use of chemical dispersant to treat an oil spill after the initial release. The natural and chemically enhanced dispersion of four oil products (dilbit, dilynbit, synbit and conventional crude) were investigated in a wave tank. Experiments were conducted in spring and summer to capture the impact of temperature, and the conditions in the tank were of breaking waves with a wave height of 0.4 m. The results showed that natural dispersion effectiveness (DE) was less than 10%. But the application of dispersant increased the DE by an order of magnitude with a statistically significant level (p

Comparison of fatigue responses and rapid force characteristics between explosive- and traditional-resistance-trained males - Cameron S. Mackey; Ryan M. Thiele; Eric C. Conchola; Jason M. DeFreitas (European Journal of Applied Physiology, 2018)

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

Rising synchrony controls western North American ecosystems - Bryan A. Black; Peter van der Sleen; Emanuele Di Lorenzo; Daniel Griffin; William J. Sydeman; Jason B. Dunham; Ryan R. Rykaczewski; Marisol García‐Reyes; Mohammad Safeeq; Ivan Arismendi; Steven J. Bograd (Global Change Biology, 2018)
Along the western margin of North America, the winter expression of the North Pacific High (NPH) strongly influences interannual variability in coastal upwelling, storm track position, precipitation, and river discharge. Coherence among these factors induces covariance among physical and biological processes across adjacent marine and terrestrial ecosystems. Here, we show that over the past century the degree and spatial extent of this covariance (synchrony) has substantially increased, and is coincident with rising variance in the winter NPH. Furthermore, centuries‐long blue oak ( Quercus douglasii ) growth chronologies sensitive to the winter NPH provide robust evidence that modern levels of synchrony are among the highest observed in the context of the last 250 years. These trends may ultimately be linked to changing impacts of the El Niño Southern Oscillation on midlatitude ecosystems of North America. Such a rise in synchrony may destabilize ecosystems, expose populations to higher risks of extinction, and is thus a concern given the broad biological relevance of winter climate to biological systems.

Predictive ability of genomic selection models in a multi-population perennial ryegrass training set using genotyping-by-sequencing - Marty J. Faville; Siva Ganesh; Mingshu Cao; M. Z. Zulfi Jahufer; Timothy P. Bilton; H. Sydney Easton; Douglas L. Ryan; Jason A. K. Trethewey; M. Philip Rolston; Andrew G. Griffiths; Roger Moraga; Casey Flay; et al. (Theoretical and Applied Genetics, 2018)

Non-auditory, electrophysiological potentials preceding dolphin biosonar click production - James J. Finneran; Jason Mulsow; Ryan Jones; Dorian S. Houser; Alyssa W. Accomando; Sam H. Ridgway (Journal of Comparative Physiology A, 2018)

Improving our science: the evolution of butterfly sampling and surveying methods over time - Katherine Kral; Jason Harmon; Ryan Limb; Torre Hovick (Journal of Insect Conservation, 2018)

Variation in grazing management practices supports diverse butterfly communities across grassland working landscapes - Cayla R. Bendel; Torre J. Hovick; Ryan F. Limb; Jason P. Harmon (Journal of Insect Conservation, 2018)

Using growth rates to estimate age of the sea turtle barnacle Chelonibia testudinaria - Sophie A. Doell; Rod M. Connolly; Colin J. Limpus; Ryan M. Pearson; Jason P. van de Merwe (Marine Biology, 2017)

Aquatic biodiversity in forests: a weak link in ecosystem services resilience - Brooke E. Penaluna; Deanna H. Olson; Rebecca L. Flitcroft; Matthew A. Weber; J. Ryan Bellmore; Steven M. Wondzell; Jason B. Dunham; Sherri L. Johnson; Gordon H. Reeves (Biodiversity and Conservation, 2017)

The time course of short-term hypertrophy in the absence of eccentric muscle damage - Matt S. Stock; Jacob A. Mota; Ryan N. DeFranco; Katherine A. Grue; A. Unique Jacobo; Eunhee Chung; Jordan R. Moon; Jason M. DeFreitas; Travis W. Beck (European Journal of Applied Physiology, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Modeling What We Sample and Sampling What We Model: Challenges for Zooplankton Model Assessment - Jason D. Everett; Mark E. Baird; Pearse Buchanan; Cathy Bulman; Claire Davies; Ryan Downie; Chris Griffiths; Ryan Heneghan; Rudy J. Kloser; Leonardo Laiolo; Ana Lara-Lopez; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2017)

3D Printing of Calcium Phosphate Ceramics for Bone Tissue Engineering and Drug Delivery - Ryan Trombetta; Jason A. Inzana; Edward M. Schwarz; Stephen L. Kates; Hani A. Awad (Annals of Biomedical Engineering, 2017)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Reduced-Dimension Modeling Approach for Simulating Recruitment/De-recruitment Dynamics in the Lung - Jason Ryans; Hideki Fujioka; David Halpern; Donald P. Gaver (Annals of Biomedical Engineering, 2016)

Zooplankton Are Not Fish: Improving Zooplankton Realism in Size-Spectrum Models Mediates Energy Transfer in Food Webs - Ryan F. Heneghan; Jason D. Everett; Julia L. Blanchard; Anthony J. Richardson (Frontiers in Marine Science, 2016)

Cytotoxic oplopane sesquiterpenoids from Arnoglossum atriplicifolium - Jason A. Clement; Rachel M. Bleich; Hailey E. Campbell; Kristin Naylor; Matthew J. Flood; Ryan M. Kelly; Shi-Biao Wu; Edward J. Kennelly; Jeffrey D. Schmitt (Natural Product Research, 2016)

A quantitative assessment of precipitation associated with the ITCZ in the CMIP5 GCM simulations - Ryan E. Stanfield; Jonathan H. Jiang; Xiquan Dong; Baike Xi; Hui Su; Leo Donner; Leon Rotstayn; Tongwen Wu; Jason Cole; Eiki Shindo (Climate Dynamics, 2016)

Impacts of climatic variation on trout: a global synthesis and path forward - Ryan P. Kovach; Clint C. Muhlfeld; Robert Al-Chokhachy; Jason B. Dunham; Benjamin H. Letcher; Jeffrey L. Kershner (Reviews in Fish Biology and Fisheries, 2016)

Bryostatin-1 Restores Blood Brain Barrier Integrity following Blast-Induced Traumatic Brain Injury - Brandon P. Lucke-Wold; Aric F. Logsdon; Kelly E. Smith; Ryan C. Turner; Daniel L. Alkon; Zhenjun Tan; Zachary J. Naser; Chelsea M. Knotts; Jason D. Huber; Charles L. Rosen (Molecular Neurobiology, 2015)

Ecoregional, catchment, and reach-scale environmental factors shape functional-trait structure of stream fish assemblages - Allison A. Pease; Jason M. Taylor; Kirk O. Winemiller; Ryan S. King (Hydrobiologia, 2015)

Ecophysiological diversity of a novel member of the genus Alteromonas, and description of Alteromonas mediterranea sp. nov. - Elena P. Ivanova; Mario López-Pérez; Mila Zabalos; Song Ha Nguyen; Hayden K. Webb; Jason Ryan; Kiril Lagutin; Mikhail Vyssotski; Russell J. Crawford; Francisco Rodriguez-Valera (Antonie van Leeuwenhoek, 2015)

Best Practices for the Development, Scale-up, and Post-approval Change Control of IR and MR Dosage Forms in the Current Quality-by-Design Paradigm - Glenn A. Van Buskirk; Satish Asotra; Christopher Balducci; Prabir Basu; Gerald DiDonato; Angelica Dorantes; W. Mark Eickhoff; Tapash Ghosh; Mario A. González; Theresa Henry; Matthew Howard; Jason Kamm; et al. (AAPS PharmSciTech, 2014)

Linking climate change projections for an Alaskan watershed to future coho salmon production - Jason C. Leppi; Daniel J. Rinella; Ryan R. Wilson; Wendy M. Loya (Global Change Biology, 2014)

Temporal dynamics of plant community regeneration sources during tallgrass prairie restoration - Jason E. Willand; Sara G. Baer; David J. Gibson; Ryan P. Klopf (Plant Ecology, 2013)

Effects of an epilepsy-causing mutation in the SCN1A sodium channel gene on cocaine-induced seizure susceptibility in mice - Ryan H. Purcell; Ligia A. Papale; Christopher D. Makinson; Nikki T. Sawyer; Jason P. Schroeder; Andrew Escayg; David Weinshenker (Psychopharmacology, 2013)

Cloning of a hamster anti-mouse CD79B antibody sequences and identification of a new hamster immunoglobulin lambda constant IGLC gene region - Ryan Haggart; Jason Perera; Haochu Huang (Immunogenetics, 2013)

Dynamic Conservation of Forest Genetic Resources in 33 European Countries - FRANÇOIS LEFÈVRE; JARKKO KOSKELA; JASON HUBERT; HOJKA KRAIGHER; ROMAN LONGAUER; DITTE C. OLRIK; SILVIO SCHÜLER; MICHELE BOZZANO; PARASKEVI ALIZOTI; REMIGIJUS BAKYS; CATHLEEN BALDWIN; DALIBOR BALLIAN; et al. (Conservation Biology, 2013)
Dynamic conservation of forest genetic resources (FGR) means maintaining the genetic diversity of trees within an evolutionary process and allowing generation turnover in the forest. We assessed the network of forests areas managed for the dynamic conservation of FGR (conservation units) across Europe (33 countries). On the basis of information available in the European Information System on FGR (EUFGIS Portal), species distribution maps, and environmental stratification of the continent, we developed ecogeographic indicators, a marginality index, and demographic indicators to assess and monitor forest conservation efforts. The pan‐European network has 1967 conservation units, 2737 populations of target trees, and 86 species of target trees. We detected a poor coincidence between FGR conservation and other biodiversity conservation objectives within this network. We identified 2 complementary strategies: a species‐oriented strategy in which national conservation networks are specifically designed for key target species and a site‐oriented strategy in which multiple‐target units include so‐called secondary species conserved within a few sites. The network is highly unbalanced in terms of species representation, and 7 key target species are conserved in 60% of the conservation units. We performed specific gap analyses for 11 tree species, including assessment of ecogeographic, demographic, and genetic criteria. For each species, we identified gaps, particularly in the marginal parts of their distribution range, and found multiple redundant conservation units in other areas. The Mediterranean forests and to a lesser extent the boreal forests are underrepresented. Monitoring the conservation efficiency of each unit remains challenging; however, Conservación Dinámica de Recursos Genéticos Forestales en 33 Países Europeos

Greater phosphorus uptake in forested headwater streams modified by clearfell forestry - Ryan M. Burrows; Jason B. Fellman; Regina H. Magierowski; Leon A. Barmuta (Hydrobiologia, 2013)

Decomposition of urban atmospheric carbon in Sonoran Desert soils - Jason P. Kaye; Sara E. Eckert; Daniel A. Gonzales; Jonathan O. Allen; Sharon J. Hall; Ryan A. Sponseller; Nancy B. Grimm (Urban Ecosystems, 2011)

Comparison of Methods for Chemical Conjugation of an Influenza Peptide to Wild-Type and Cysteine-Mutant Virus-Like Particles Expressed in Pseudomonas fluorescens - Greg T. Cantin; Sol Resnick; Hongfan Jin; Ryan O’Hanlon; Octavio Espinosa; Alex Stevens; Jason Payne; Nicole R. Glenn; Lada Rasochova; Jeffrey R. Allen (International Journal of Peptide Research and Therapeutics, 2011)

Effect of Ocean Acidification on the Speciation of Metals in Seawater - Frank Millero; Ryan Woosley; Benjamin DiTrolio; Jason Waters (Oceanography, 2009)

Identification of transposons, retroelements, and a gene family predominantly expressed in floral tissues in chromosome 3DS of the hexaploid wheat progenitor Aegilops tauschii - Ryan Whitford; Ute Baumann; Tim Sutton; Luke Gumaelius; Petra Wolters; Scott Tingey; Jason A. Able; Peter Langridge (Functional & Integrative Genomics, 2006)

Variation in scale numbers is consistent with ecologically based natural selection acting within and between lizard species - Ryan Calsbeek; Jason H. Knouft; Thomas B. Smith (Evolutionary Ecology, 2006)

Contribution of 5′- and 3′-untranslated regions of plastid mRNAs to the expression of Chlamydomonas reinhardtii chloroplast genes - Dwight Barnes; Scott Franklin; Jason Schultz; Ryan Henry; Emma Brown; Anna Coragliotti; Stephen P. Mayfield (Molecular Genetics and Genomics, 2005)